Impaired intracortical transmission in G2019S leucine rich‐repeat kinase Parkinson patients. Issue 5 (10th February 2017) - Ponzo, Viviana; Di Lorenzo, Francesco; Brusa, Livia; Schirinzi, Tommaso; Battistini, Stefania; Ricci, Claudia; Sambucci, Manolo; Caltagirone, Carlo; Koch, Giacomo
ABSTRACT: Objectives : A mutation in leucine‐rich repeat kinase 2 is the most common cause of hereditary Parkinson's disease (PD), yet the neural mechanisms and the circuitry potentially involved are poorly understood. Methods : We used different transcranial magnetic stimulation protocols to explore in the primary motor cortex the activity of intracortical circuits and cortical plasticity (long‐term potentiation) in patients with the G2019S leucine‐rich repeat kinase 2 gene mutation when compared with idiopathic PD patients and age‐matched healthy subjects. Paired pulse transcranial magnetic stimulation was used to investigate short intracortical inhibition and facilitation and short afferent inhibition. Intermittent theta burst stimulation, a form of repetitive transcranial magnetic stimulation, was used to test long‐term potentiation‐like cortical plasticity. Leucine‐rich repeat kinase 2 and idiopathic PD were tested both in ON and in OFFl ‐dopa therapy. Results : When compared with idiopathic PD and healthy subjects, leucine‐rich repeat kinase 2 PD patients showed a remarkable reduction of short intracortical inhibition in both ON and in OFFl ‐dopa therapy. This reduction was paralleled by an increase of intracortical facilitation in OFFl ‐dopa therapy. Leucine‐rich repeat kinase 2 PD showed abnormal long‐term potentiation‐like cortical plasticity in ONl ‐dopa therapy. Discussion : The motor cortex in leucine‐rich repeat kinase 2 mutated PD patients is strongly disinhibited and hyperexcitable. These abnormalities could be a result of an impairment of inhibitory (gamma‐Aminobutyric acid) transmission eventually related to altered neurotransmitter release. © 2017 International Parkinson and Movement Disorder Society